Eksistensi dan Dinamika Peradilan Agama di Indonesia: Peran, Tantangan, dan Perkembangannya dalam Sistem Hukum Nasional: The Existence and Dynamics of Religious Courts in Indonesia: Roles, Challenges, and Developments within the National Legal System - Aditia M. Yusup; Samsuddin, Samsuddin; Kasman Bakry (DIRASAH: Jurnal Kajian Islam, 2024)
This article examines the existence and dynamics of Religious Courts in Indonesia, emphasizing their crucial role in addressing Islamic legal issues such as marriage, inheritance, and other civil matters. From the Islamic kingdoms to the modern era, Religious Courts have played a strategic role, despite facing various challenges during colonial rule and in post-independence times. The purpose of this article is to explore the roles, challenges, and developments of Religious Courts within Indonesia's national legal system. The research methodology employed is a qualitative literature review, analyzing various legal sources and court rulings. The findings indicate that, despite significant progress, Religious Courts continue to face challenges, particularly in integrating with the national legal system and adapting to modernization. The conclusion suggests that Religious Courts remain crucial in delivering justice for the Muslim community, though stronger synergy with the national legal system is necessary. The implications of this research contribute to the development of legal scholarship, particularly in strengthening the role of Religious Courts in Indonesia. The study also provides recommendations for policymakers in formulating more effective regulations to address the contemporary challenges faced by Religious Courts.